A clinico-epidemiological study on childhood vitiligo - Neerja Puri (Wolters Kluwer Medknow Publications, 2016)
Introduction: Vitiligo is a disorder of melanocytes which may have a significant effect on the psyche of a patient. Aims: To study the clinical profile of the patients with childhood vitiligo and see the association of vitiligo with other autoimmune diseases. Methods: A randomized controlled prospective study was done of thirty patients of childhood vitiligo aged below14 years of age. Results: Vitiligo vulgaris was the most common type of vitiligo seen in 50% children followed by focal and segmental vitiligo in 20% each followed by acrofacial vitiligo in 10% children.